3. A Theoretical Study of the Relationships Between Electronic Structure and Inhibitory Effects of Caffeine Derivatives on Neoplastic Transformation - KPOTIN, ASSONGBA GASTON; KANKINOU, S. Gautier; KUEVI, URBAIN AMAH; GOMEZ-JERIA, Juan Sebastian; MENSAH, JEAN-BAPTISTE (My University, 2017)
A DFT study of the relationships between electronic structure and inhibitory effects of caffeine derivatives on neoplastic transformation was carried out. We obtain one statistically significant equation (R=0.97, R²= 0.94, adjusted R²= 0.92, F(7,34) =71.40 (p<0.00001), SD=0.14), relating the variation of the biological activity with the variation of the values of a definite set of local atomic reactivity indices. Based on the analysis of the results, a partial pharmacophore was built that can be employed as a tool for the development of more active molecules. Calculations have been performed by DFT/B3LYP method in the 6-31G orbital basis set.
Keywords: Caffeine; anticancer; QSAR; pharmacophore; DFT; electronic structure